A cubic polynomial
f ( x ) = 8 x 3 − 3 x 2 − 3 x − 1
has one real root of the form c 3 a + 3 b + 1 , where a , b , c are positive integers. Find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes, thank you, Daniel!
It is OK to share nice problems you have come across, provided that the solution is not obviously available on the Internet, and that you give proper credit. In particular, if you want to share an AIME problem, modify it before submitting and indicate that your problem is based on an AIME problem. You may also want to reveal the exact source afterwards. The recent AIME problems should probably be avoided altogether unless they can be SUBSTANTIALLY modified.
Oh man! I do not these stealings!
User "Bruce Wayne" has done the same thing yesterday with three problems from Nick's Mathematical Puzzles.
We should be able to "flag" these problems.
Wow this was a difficult problem. But how on earth did you rationalise that denominator?
Log in to reply
The factorization that ( a − b ) ( a 2 + a b + b 2 ) = a 3 − b 3 .
Yea, I knew that I saw this problem before.
Awesome! Daniel
I really liked the simplicity of this (apparently hard) problem.
Let's rewrite f ( x ) = 8 x 3 − 3 x 2 − 3 x − 1 as f ( x ) = 9 x 3 − ( x + 1 ) 3 .
Knowing ( a − b ) ( a 2 + a b + b 2 ) = a 3 − b 3 , we can simplify f ( x ) to ( 3 9 x − x − 1 ) ( 3 8 1 + 3 9 ( x − 1 ) + ( x − 1 ) 2 ) = 0 .
It is clear that the expression 3 9 x − x − 1 = 0 holds the real root. Thus x = 3 9 − 1 1 .
Remembering ( a − 1 ) ( a 2 + a + 1 ) = x 3 − 1 , we can use this trick to simplify x 's fraction to x = 8 3 8 1 + 3 9 + 1 . Thus a + b + c = 9 8 .
Let y = x − 8 1 , then 8 x 3 − 3 x 2 − 3 x − 1 = 0 ⟺ x 3 − 8 3 x 2 − 8 3 x − 8 1 = 0 ⟺ y 3 − 6 4 2 7 y − 5 1 2 9 0 = 0 . Now if y = u + v then y 3 − 3 u v y − ( u 3 + v 3 ) = 0 has root y = u + v . I need 6 4 9 = u v and 5 1 2 9 0 = u 3 + v 3 . From these two equations, u 6 − 5 1 2 9 0 u 3 + 6 4 3 9 3 = 0 so u 3 = 2 1 ( 5 1 2 9 0 + 5 1 2 2 9 0 2 − 4 6 4 3 9 3 ) and v 3 = 2 1 ( 5 1 2 9 0 − 5 1 2 2 9 0 2 − 4 6 4 3 9 3 ) Therefore y = 3 2 1 ( 5 1 2 9 0 + 5 1 2 2 9 2 ⋅ 1 0 2 − 4 6 4 3 9 3 ) + 3 2 1 ( 5 1 2 9 0 − 5 1 2 2 9 2 ⋅ 1 0 2 − 4 6 4 3 9 3 ) y = 3 2 1 0 1 ( 9 0 + 9 2 ( 1 0 0 − 4 ⋅ 9 ) ) + 3 2 1 0 1 ( 9 0 − 9 2 ( 1 0 0 − 4 ⋅ 9 ) ) y = 3 2 1 0 1 ( 9 0 + 7 2 ) + 3 2 1 0 1 ( 9 0 − 7 2 ) y = 8 3 + 3 3 2 ⟺ x = 8 8 1 3 1 + 9 3 1 + 1 a + b + c = 9 8
Quite the bulldozer you've used to dig a 3 inch hole in soil...
Log in to reply
Yes, very inelegant and time consuming. I regret posting this after seeing the simplicity of the other solutions.
Log in to reply
Even though it is not a good way, but it is still one of the way to approach it
By applying cardano's method ,we get the real root as: x = 8 3 3 4 + 3 3 2 + 1 Hence, a = 81, b = 9, c = 8 ⇒ a + b + c = 8 1 + 9 + 8 = 9 8
f(x) = 0 adding x cubed to both sides yields 9x^3 = x^3 +3x^2 +3x +1 = (x+1)^3 taking cube root of both sides and then solving for x and rationalizing the denominator, x = (cubert (81) + cubert (9) + 1)/8 so the answer is 98
Problem Loading...
Note Loading...
Set Loading...
We have that 9 x 3 = ( x + 1 ) 3 , so it follows that 3 9 x = x + 1 . Solving for x yields 3 9 − 1 1 = 8 3 8 1 + 3 9 + 1 , so the answer is 0 9 8 .
This user blatantly stole the problem from the 2013 AIME I problem 5. It seems fitting that I should, similarly, blatantly copy a solution that can be found here: http://www.artofproblemsolving.com/Wiki/index.php/2013 AIME I Problems/Problem 5
@devansh shringi: It is OK for you to get inspiration from other problems, but it is not OK to just copy them and submit them as your own.